PEMANFAATAN BUAH BELIMBING MANIS (Averrhoa carambola L.) DAN BUAH NANAS (Ananas comosus L.) DALAM PEMBUATAN PERMEN JELLY - Martia Ramadani Siregar; Noviar Harun; Yusmarini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to obtain the ratio of sweet star fruit extracts and pineapple extracts selected in the manufactur of jelly candy. This research used Complete Randomized Design (CRD) with five treatments and four replications which were followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research included B1N1 (ratio of sweet star fruit extracts and pineapple extracts 90 : 10), B2N2 (ratio of sweet star fruit extracts and pineapple extracts 80 : 20), B3N3 (ratio of sweet star fruit extracts and pineapple extracts 70 : 30), B4N4 (ratio of sweet star fruit extracts and pineapple extracts 60 : 40) and B5N5 (ratio of sweet star fruit extracts and pineapple extracts 50 : 50). The result of analysis showed that the ratio of sweet star fruit extracts and pineapple extracts significantly affect on moisture content, ash content, pH, pectin content, reduction sugar content, colour, flavor, texture and overall assessment but did not significantly of taste of jelly candy. The best formulation jelly candy was B3N3 with water 7,88%; ash 0,65%; pH 4,21; pectin 2,54%; sugar reduction 22,93%. Organoleptic scores of  B3N3 were 2,23 (colour), 3,17 (flavour), 2,27 (taste), 2,67 (texture) and 2,23 (comprehersive score).   Keywords: jelly candy, sweet star fruit and pineapple